Nutrition Education Through by Smart Books of Anemia Prevention on the Behavior of Pregnant Women at the Puntikayu Health Center Palembang - Mardiana Mardiana; Yulianto Yulianto (Universitas Islam Lamongan, 2021)
According to WHO, the global prevalence of anemia in pregnant women is 41.8%. Iron deficiency anemia in pregnant women increases the risk of bleeding, preeclampsia, and infection. Pregnant women who suffer from iron deficiency anemia are also risky birth a babies with low birth weight, stunting (short.) The type of this research is a Pre and Post Quasi Experimental Research with The Intervention of Nutrition Education through the Anemia Prevention Smart Book. The sample in this study were 45 pregnant women using the Simple Random Sampling technique. Paired sample t test – Knowledge test, obtained p value = 0.000 means that there is a significant difference in knowledge before and after the nutrition education is given through the anemia prevention smart book. Paired sample t-test Attitude test, obtained p value = 0.002 means there is a significant difference in attitudes before and after being given nutrition education through the smart book on anemia prevention. Paired sample t-test action, obtained p value = 0.000 means that there is a significant difference before and after the action was given nutrition education through the anemia prevention smart book.